Pengetahuan dan sikap penjamah makanan terhadap higiene sanitasi makanan di Toko Kue XY Tasikmalaya - Oktaviani, Ersya Sri; Dika, Nidya Elpara; Salsabila, Salwa; Muldani, Muhammad Defrian; Putri, Azka Megistriani; Gifari, Agi Ahmad; Annashr, Nissa Noor (Program Studi Gizi, 2025)
This study aims to determine the extent of the application of food hygiene and sanitation principles at XY Cake Shop in Tasikmalaya City. This study uses a quantitative method with a cross-sectional study design. The population consists of all 35 shop employees who were sampled through total sampling techniques. Data were collected using a Google Form questionnaire and observation with a checklist sheet. The results showed that 57.1% of respondents had high knowledge about food hygiene and sanitation, especially in terms of personal hygiene and the use of safe food additives (BTP). Most (more than 80%) showed a positive attitude towards the use of natural BTP and the importance of supervision from health agencies. As many as 97.1% stated that they had used BTP according to the provisions and 100% did not use hazardous materials. However, only 25.7% of respondents had attended training related to BTP. The Chi-Square test showed a significant relationship between knowledge and behavior (p = 0.006), and attitude and behavior (p = 0.002). These findings indicate that improving the behavior of food handlers can be achieved through strengthening aspects of knowledge and attitudes, as well as ongoing training. This study recommends increasing human resource capacity and regular supervision to ensure food safety in micro and medium-scale businesses.